Bone Defect Repair Using a Bone Substitute Supported by Mesenchymal Stem Cells Derived from the Umbilical Cord - Michal Kosinski; Anna Figiel-Dabrowska; Wioletta Lech; Lukasz Wieprzowski; Ryszard Strzalkowski; Damian Strzemecki; Lukasz Cheda; Jacek Lenart; Krystyna Domanska-Janik; Anna Sarnowska (Stem Cells International)
Objective. Bone defects or atrophy may arise as a consequence of injury, inflammation of various etiologies, and neoplastic or traumatic processes or as a result of surgical procedures. Sometimes the regeneration process of bone loss is impaired, significantly slowed down, or does not occur, e.g., in congenital defects. For the bone defect reconstruction, a piece of the removed bone from ala of ilium or bone transplantation from a decedent is used. Replacement of the autologous or allogenic source of the bone-by-bone substitute could reduce the number of surgeries and time in the pharmacological coma during the reconstruction of the bone defect. Application of mesenchymal stem cells in the reconstruction surgery may have positive influence on tissue regeneration by secretion of angiogenic factors, recruitment of other MSCs, or differentiation into osteoblasts. Materials and Methods. Mesenchymal stem cells derived from the umbilical cord (Wharton’s jelly (WJ-MSC)) were cultured in GMP-grade DMEM low glucose supplemented with heparin, 10% platelet lysate, glucose, and antibiotics. In vitro WJ-MSCs were seeded on the bone substitute Bio-Oss Collagen® and cultured in the StemPro® Osteogenesis Differentiation Kit. During the culture on the 1st, 7th, 14th, and 21st day (day in vitro (DIV)), we analyzed viability (confocal microscopy) and adhesion capability (electron microscopy) of WJ-MSC on Bio-Oss scaffolds, gene expression (qPCR), and secretion of proteins (Luminex). In vivo Bio-Oss® scaffolds with WJ-MSC were transplanted to trepanation holes in the cranium to obtain their overgrowth. The computed tomography was performed 7, 14, and 21 days after surgery to assess the regeneration. Results. The Bio-Oss® scaffold provides a favourable environment for WJ-MSC survival. WJ-MSCs in osteodifferentiation medium are able to attach and proliferate on Bio-Oss® scaffolds. Results obtained from qPCR and Luminex® indicate that WJ-MSCs possess the ability to differentiate into osteoblast-like cells and may induce osteoclastogenesis, angiogenesis, and mobilization of host MSCs. In animal studies, WJ-MSCs seeded on Bio-Oss® increased the scaffold integration with host bone and changed their morphology to osteoblast-like cells. Conclusions. The presented construct consisted of Bio-Oss®, the scaffold with high flexibility and plasticity, approved for clinical use with seeded immunologically privileged WJ-MSC which may be considered reconstructive therapy in bone defects.